Epidemiology of Injuries to Early Adolescents from Family Violence Evaluated in an Urban Pediatric Emergency Department. Issue 3 (28th March 2023) - Miller, Mattea; Jones, Vanya; Walter, Creason; Manning Ryan, Leticia
Abstract : Background: Exposure to family violence during childhood and adolescence increases the risk for experiencing or perpetrating future violence. Social distancing protocols combined with reduction in access to youth/family services during the COVID-19 pandemic may have intensified the risk of exposure to familial violence. Objectives: This study describes the epidemiology of violence-related injuries to 10- to 15-year-old children from family violence, including child maltreatment and physical fighting, resulting in emergency department (ED) evaluation. Methods: This retrospective cohort study located in an urban academic pediatric ED in the mid-Atlantic region is a review of electronic medical records between January 2019 and March 2020 (prepandemic period) and March to December 2020 (pandemic period). This review focused on visits for youth aged 10 to 15 years who presented for evaluation of an injury due to a violent event involving a family member. Demographic and clinical data were abstracted, including circumstances of the event. Descriptive statistics were used to summarize data and compare prepandemic to postpandemic proportions. Results: Of 819 youth aged 10 to 15 years evaluated for a violence-related injury, 448 (54.7%) involved a family member. Of these, most involved parents/guardians, 343 (76.6%), and occurred at home (83.9%). Most patients were girls (54.0%), Black/African American (84.4%), and were enrolled in a public insurance plan (71.2%). Most youth were transported to the hospital by police (66.7%). Overall, alcohol, drugs, and weapons were involved in 10.0%, 6.5%, and 10.7% of events, respectively, and their involvement significantly increased during the pandemic period to 18.8%, 14.9%, and 23.8% ( P < 0.001). Most patients (98.7%) were discharged from the ED. Conclusions: More than half of violence-related injuries treated in the ED in this population resulted from family violence. Family violence is a prevalent and possibly underrecognized cause of injuries during adolescence. Further research should explore the potential of the ED as a setting for preventive interventions.